Strategies for the Conservation of Interior Spaces in Historic Buildings (Al-Academy, 2026)
The study aims to explore modern strategies and methods appropriate for preserving the authenticity of interior spaces in historic buildings worldwide.The study adopted the case study approach to analyze the study model, as it is the appropriate approach to achieve the current research objective and to arrive at accurate results. The theoretical framework includes the concept of strategy, methods for preserving interior spaces, and global applications through a review of relevant literature and sources. The analysis focused on the case study of the Notre Dame Cathedral, the main nave. The study consists of three chapters: methodology, theoretical framework, and research findings and recommendations.The study concluded that modern conservation strategies utilize innovative tools and advanced materials to reduce the need for maintenance while preserving authenticity. They also offer a comprehensive approach that integrates historical, cultural, and social aspects, with the flexibility to adapt to modern changes.Rapid changes require a balanced approach to the conservation of historic buildings, combining a scientific understanding of their physical and moral nature with traditional and modern techniques. Conservation methods, whether preventive, technical, or restorative, must adapt to the building's condition and its historical, environmental, physical, and cultural context